SSR Markers Facilitate Testing of Genetic Purity and Prediction of Biological Parents for Breeding Crosses of Oil Palm - Norhalida Mohamed Serdari; Ting Ngoot-Chin; Rajinder Singh; Kandha Sritharan; Maryam Mohamed Rehan; Jalani Bin Sukaimi; Maizura Ithnin (Malaysian Palm Oil Board, 2026)
Indexed by MYCITE